THE USE OF AUDIO-LINGUAL METHOD IN TEACHING ENGLISH - Diyora Umarkulova (PEDAGOGS, 2024)
Abstract. The audio-lingual method (ALM) dominated English language teaching (ELT) in the mid-20th century. This article explores the core principles of the ALM, its strengths and weaknesses, and its relevance in modern language learning. While largely superseded by communicative approaches, the ALM’s legacy offers valuable insights. The article concludes by highlighting the importance of a balanced approach in ELT that promotes both accuracy and fluency within a context of meaningful communication.